2001
DOI: 10.2190/v06d-2lxr-e3f6-9r6y
|View full text |Cite
|
Sign up to set email alerts
|

Religiousness as a Predictor of Alcohol Use in High School Students

Abstract: The purpose of this study was to examine the relationship between religiousness and alcohol use of adolescents. A sample of high school seniors was drawn based on the second follow-up National Educational Longitudinal Study of 1988 (NELS:88). Multiple regression was employed using a hierarchical strategy to determine the impact of religiousness on alcohol use when accounting for other factors that have been shown to affect alcohol use. The results provide support for examining religiousness variables as predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…For rare religious service attendance, both adolescents and adults had a higher frequency of alcohol use for first use, current use, and regular use. These findings are consistent with the findings of Brown et al (2001) and Park et al (2001) who reported that frequency of religious service attendance is a good predictor variable of alcohol use.…”
Section: Frequency Of Religious Service Attendancesupporting
confidence: 93%
“…For rare religious service attendance, both adolescents and adults had a higher frequency of alcohol use for first use, current use, and regular use. These findings are consistent with the findings of Brown et al (2001) and Park et al (2001) who reported that frequency of religious service attendance is a good predictor variable of alcohol use.…”
Section: Frequency Of Religious Service Attendancesupporting
confidence: 93%
“…Although few studies have examined the relationship between religiosity and alcohol use in college students, studies using adolescent and adult samples are encouraging. For example, Park, Bauer, and Oescher (2001) found that for African American adolescents, intrinsic, subjective components of religion (e.g., the importance of religion to a person), but not extrinsic, behavioral components of religion (e.g., church attendance), significantly predicted alcohol use, even after controlling for socioeconomic status, gender, family interaction, academic achievement, time spent on extracurricular activities, self esteem, and locus of control. Bowie et al (2006) longitudinally studied the effects of religiosity, social resources, and mental health on alcohol use problems in African American adults and found that, among those who were depressed, frequent churchgoers had significantly fewer alcohol use problems than their less frequent churchgoing counterparts.…”
Section: Religiositymentioning
confidence: 99%
“…The religiosity-substance use relation might be moderated by race (Park et al, 2001; Steinman et al, 2008). Even though a recent meta-analysis indicated a stronger negative correlation between religiosity/spirituality and substance use in white versus non-white individuals (Yonker et al, 2011), most existing research has focused only on racial differences across Caucasians and African Americans (Brown et.…”
Section: Introductionmentioning
confidence: 99%